The introduction of ICTs in the design of sanitary architectural environments, as a tool to help patients’ therapy (2017)
There is a reasonable number of documents on the design of hospitals and related buildings, and even on mental health facilities, but there are no psychological benefits studies for the basic design elements that are mandatory in mental health institutions. This work analyzes different aspects of ambient design dealing with seemingly minor interior choices such as texture, color, sounds / noises, decoration, and all the elements that create a mood. In doing so, we should be able to see how design decisions can affect patients’ health outcomes and prove that spatial ambiences can be used to improve health, and mental health in particular. For this, a field study was conducted on a sample chosen at the Er Rasi psychiatric hospital in Annaba, in Algeria, as well as the neurology department at the Annaba University Hospital. These two categories of patients are extremely reactive and receptive to the atmosphere of the space that surrounds them, a key factor that motivated our choice. Interdisciplinary and trans-sensorial aspects, common to analysis and design, rooted in the concept of spatial atmosphere, encourage us to use the NICT (New Information and Communication Technologies) as a tool for the creation of an interactive living space evolving in real time capable of spontaneously modifying the physical properties of space, depending on the environment, to serve as a therapy for depressed people in a psychiatric environment.